ChemInform Abstract: An Alternative to the Classical α‐Arylation: The Transfer of an Intact 2‐Iodoaryl from ArI(O2CCF3)2. Issue 13 (March 2015) - Jia, Zhiyu; Galvez, Erik; Sebastian, Rosa Maria; Pleixats, Roser; Alvarez‐Larena, Angel; Martin, Eddy; Vallribera, Adelina; Shafir, Alexandr
Abstract The reaction of activated ketones such as (I), (IV), and (VI) with phenylbis(trifluoroacetoxy)iodane (II) leads to the corresponding α‐(2‐iodoaryl)ketones.